Legal Review of Criminal Law Regulations in Money Laundering Cases - Trissetianto, Andri Catur; Ridwan (Siber International Journal of Advanced Law (SIJAL), 2024)
This study examines the effectiveness of Indonesia’s legal framework for combating money laundering, focusing on Law No. 8 of 2010 on the Prevention and Eradication of Money Laundering (UU PTPPU). Through a comprehensive legal analysis, case studies, and a comparative review with international standards, the research reveals that while the law has laid a solid foundation for anti-money laundering efforts, its practical implementation faces significant challenges. Key findings show that 45% of the results indicate the law is effective in providing a formal structure for regulating financial institutions and criminalizing money laundering activities. However, 30% of findings highlight enforcement challenges, such as limited resources, inadequate technological tools, and coordination issues among agencies. 15% of the findings reveal legal gaps, particularly in addressing emerging financial technologies such as cryptocurrencies and digital finance platforms, which have become new avenues for money laundering. The study also found that 70% of law enforcement agencies face substantial difficulties in investigating complex financial transactions, and 50% of financial institutions struggle with compliance due to outdated systems and insufficient training. 60% of regulatory bodies such as PPATK also face challenges in effectively overseeing financial transactions. The study further compares Indonesia's legal framework to international standards set by the Financial Action Task Force (FATF) and identifies areas where Indonesia is aligned with global recommendations but lags in technology adoption and cross-border cooperation. Based on these findings, the study recommends strengthening regulatory oversight, investing in law enforcement capacity, and updating the legal framework to address digital finance and cryptocurrencies. Enhanced coordination between financial institutions, regulatory bodies, law enforcement, and international partners is also essential to improve the effectiveness of anti-money laundering efforts. This research offers valuable insights for policymakers and institutions to strengthen Indonesia's fight against money laundering.